KINERJA ORGANISASI PADA KOPERASI PEMBERDAYAAN UMMAT DAARUT TAUHID TANGERANG PELATIHAN AUDIT SUMBER DAYA MANUSIA UNTUK MENILAI EFEKTIVITAS SELATAN - Budiman; Nopi Oktavianti; Imbron (Abdi Jurnal Publikasi, 2025)
This Community Service activity aims to improve the capacity of the management and staff of the Daarut Tauhiid Ummat Empowerment Cooperative (KOPMU-DT) in managing human resources through an HR audit approach. To date, partner cooperatives have not had a structured and well-documented HR audit system, resulting in HR management not running optimally in supporting the achievement of organizational goals. The training was conducted face-to-face for two days by a team of lecturers from the Management Study Program at Pamulang University, and attended by participants consisting of management, managerial staff, and cooperative HR personnel. The training materials included an understanding of the basic concepts of HR audits and their urgency for organizational effectiveness, the process of developing audit instruments relevant to the cooperative's needs, practical simulations of HR audit implementation, and analysis of simulation results to formulate data-based strategic recommendations. The evaluation results showed a 45 percent increase in participant understanding as measured by pre- and post-tests. In addition, all participants demonstrated active participation throughout the activity. One important achievement of this activity is the beginning of the formation of cooperative managerial awareness to gradually compile and develop an internal HR audit system, as part of the process of improving the organizational structure and data-based decision-making. The concrete output of this activity is an HR audit instrument template tailored to the cooperative context, as well as an audit simulation report that can serve as an initial reference for implementing a sustainable HR audit system.